Anders dink anders doen. Op soek na ‘n eko-teologiese perspektief op kloning - Buitendag, Johan (Verbum et ecclesia, 2004)
The article’s departing point is the conviction that contemporary micro-biology and gene-technology have confronted Christian ethics with a reality for which it is not sufficiently equipped. The whole debate on human cloning and human stem cell research has raised the challenge of a fresh understanding of man and humanity as well as an ethic that takes the creation as a whole seriously. The question posed is whether the zygote or even the embryo in the Petri- dish, is already a human person. It is suggested that the organic and cultural environment is essential to our understanding of man. Seeing that man is the product of a bio- cultural background together with individual choices, it is by definition impossible to clone man. The responsibility of man towards the rest of creation has to be understood against the background of a socio-linguistic framework which constitutes our ethics, perhaps as virtue ethics. The implication is that morality is intrinsically connected to reality.